SAT0152 Body mass index negatively influences the response to infliximab in rheumatoid arthritis. (23rd January 2014) - Ottaviani, S.; Gardette, A.; Quintin, E.; Dawidowicz, K.; Palazzo, E.; Hayem, G.; Meyer, O.; Dieudé, P.
Abstract : Background: The excess of adipose tissue in obese individuals may have immunomodulating properties and pharmacokinetics consequences. Adipose tissue is potentially involved in the regulation of inflammation in rheumatoid arthritis (RA). Recently, an exploratory study suggested that body mass index (BMI) could affect infliximab (IFX) treatment responses in RA patients (1). Objectives: The aim of this study was to investigate whether body mass index (BMI) affects the response to IFX in RA patients. Methods: In this retrospective study were included RA patients fulfilling the ACR 1987 criteria and receiving infliximab therapy. All individuals provided informed written consent as approved by the local ethic committee board. The BMI was assessed before the initiation of IFX treatment (3 mg/kg intravenously). After 6 months of treatment, changes in disease activity (DAS28) were assessed. The primary end point was the EULAR DAS28 response. The following covariates were included for the analysis: gender, anti-CCP antibodies and RF status, mean disease duration, erythrocyte sedimentation rate (ESR), CRP level, DAS28, concomitant DMARDS therapy and corticosteroids consummation. Results: A total of 73 RA patients (age: 48.5±10.5 years, 82% of females, disease duration: 8.8±6.9 years, 77% RF+, 86% anti-CCP +) were included. At M0, BMI was 27.1±6.9 kg/m 2 . Patients were classified in 3 distinct groups according to their BMI: normal (BMI <25 kg/m 2 ), overweight (BMI [25-30] kg/m 2 ) and obesity (BMI >30 kg/m 2 ). At baseline no difference was observed between the 3 BMI subgroups according to the RA covariates, notably the DAS28. The EULAR non-response was found to be only influenced by 2 independent factors: a lower initial DAS28 (4.9±1.4 vs 5.9±1.0, P =0, 012) and a higher BMI (29.5±8.7 vs 25.2±3.9 kg/m 2, P =0.013). When the 3 BMI subgroups were independently analyzed, the negative influence of BMI on response to IFX was only found in obese patients ( P =0.008, OR 5.2 [1.3-23.2]) in comparison to normal BMI group. Conclusions: Our study supports the previously reported negative correlation between BMI and infliximab response in RA. Further prospective studies, including assessment of the fat mass, pharmacokinetics and adipokines dosages are mandatory to elucidate the role of obesity and the fat mass in modulating the RA IFX response. References: Klaasen R, Wijbrandts CA, Gerlag DM, Tak PP. Body mass index and clinical response to infliximab in rheumatoid arthritis. Arthritis Rheum 2011. Disclosure of Interest: None Declared